2020
DOI: 10.3892/or.2020.7707
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LINC00958 inhibits proliferation, invasion and migration, and promotes apoptosis of colorectal cancer cells by targeting miR‑3619‑5p

Abstract: The aberrant expression of long non-coding RNAs (lncRNAs), including LINC00958, has been demonstrated in several types cancers. The present study aimed to investigate the role of LINC00958 in colorectal cancer (CRC) and identify the possible underlying mechanisms. The expression of LINC00958 and microRNA (miR)-3619-5p was detected in several human CRC cell lines using reverse transcription-quantitative PCR. Then, short hairpin RNA (shRNA)-LINC00958 was transfected into the cells. The results revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…In addition, Brownmiller et al found a significant difference in the expression of the Y chromosome lncRNA linc-SPRY3-2/3/4 between radiation-sensitive and radiation-resistant non-small cell lung cancer cells, and confirmed that knockdown of linc-SPRY3-2/3/4 promoted cell viability and resistance to apoptosis after treatment with 8 Gy [28]. In this study, we found that LINC00958 was upregulated in colorectal cancer tissues, which was in accordance with a previous study [29]. Further analysis showed that a high level of LINC00958 was positively correlated with T stage and predicted poor overall survival and disease-free survival.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Brownmiller et al found a significant difference in the expression of the Y chromosome lncRNA linc-SPRY3-2/3/4 between radiation-sensitive and radiation-resistant non-small cell lung cancer cells, and confirmed that knockdown of linc-SPRY3-2/3/4 promoted cell viability and resistance to apoptosis after treatment with 8 Gy [28]. In this study, we found that LINC00958 was upregulated in colorectal cancer tissues, which was in accordance with a previous study [29]. Further analysis showed that a high level of LINC00958 was positively correlated with T stage and predicted poor overall survival and disease-free survival.…”
Section: Discussionsupporting
confidence: 92%
“…We screened our RNA-seq data analyzed by NONCODE database [ 18 ] obtained from clinical specimens of normal ovarian tissues ( n = 6) and ovarian cancers ( n = 15) [ 15 , 16 ]. Screening NONCODE v4 transcripts abundantly expressed in ovarian cancer compared with normal ovarian tissues by ≥10-folds at an FDR q -value threshold <0.05, we identified 10 particular lincRNAs ( Table 1 ), including known oncogenic RNAs: competing endogenous lncRNA 2 for microRNA let-7b ( CERNA2 )/ human ovarian cancer-specific transcript 2 (HOST2) [ 19 ], urothelial cancer associated 1 ( UCA1 ) [ 14 , 20 , 21 , 22 ], and long intergenic non-protein coding RNA 958 (LINC00958) [ 23 ]. CERNA2 / HOST2 was shown to promote ovarian cancer cell proliferation, partly by sponging the tumor suppressor let-7b [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary characteristics of tumors are malignant proliferation and imbalance between cell proliferation and apoptosis [ 23 ]. Inhibiting proliferation and inducing apoptosis are excellent strategies for tumor treatment [ 24 ]. Previous research has shown that GLSP and G. lucidum triterpenes in G. lucidum spore powder can effectively inhibit tumors [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%